Chronic low back pain among French healthcare workers and prognostic factors of return to work (RTW): a non-randomized controlled trial. Issue 1 (December 2015) - Cougot, B.; Petit, A.; Paget, C.; Roedlich, C.; Fleury-Bahi, G.; Fouquet, M.; Menu, P.; Dubois, C.; Geraut, C.; Roquelaure, Y.; Tripodi, D.
Abstract Background Many factors influence the return to work of workers with chronic low back pain (CLBP). They have been said to vary according to socio-professional group. This study first aimed to compare prognostic factors influencing the return to work of CLBP healthcare workers (HCWs) and other workers (non-HCWs) after rehabilitation coupled with an occupational intervention. The second objective was to improve the evolution of indicators such as clinical examination, psychosocial impact and pain impact. Methods Between 2007 and 2012, a cohort of 217 CLBP workers (54.8 %-women; mean age = 41.3 ± 9.5 years, 118 non-HCWs; 99 HCWs mainly from the public sector) was included in an ambulatory rehabilitation program (standard physiotherapy or intensive network physiotherapy) coupled with an occupational intervention. Workers completed a questionnaire and had a clinical examination at baseline and after 24 months' follow up. Physical, social and occupational data was collected at the same time. Statistical analyses were performed to evaluate prognostic factors for return to work and compare the two worker populations. Results There was no difference between groups for the rate of OP (occupational physician) intervention or type of physiotherapy. 77.3 % of workers returned to work after 2 years following inclusion. To be an HCW (OR 0.1; 95 % CI [0.03–0.34]), to have less than 112 sick- leave days (OR 1.00; 95 % CI [0.93–1.00]), a small fingertip-floor distance (OR 0.96; 95 % CI [0.93–0.99]), a low anxiety/depression score (OR 0.97; 95 % CI [0.95–1.00]), a low impact of CLBP on daily life (OR 0.96; 95 % CI [0.93–1.00]), and on quality of life (OR 0.98; 95 % CI [0.95–1.00]) at baseline were statistically associated with return to work after 2 years of follow up. Only the profession (workplace) was statistically associated with return to work after 2 years of follow up using multivariate analysis. Conclusion To our knowledge, this is the first cohort study concerning predictive factors of RTW among CLBP workers after 2 years of follow up. Interventions in the work environment did not seem to predict job retention significantly. But only 50 % of the employees in both groups (HCW and non-HCW) had one intervention at their workplace after 2 years. This study underlined the fact that the type of physiotherapy with a well-trained physiotherapist used to take care of CLBP could not impact on the RTW forecast. To develop these initial results, it might be interesting to study the comparison between private and public sectors and to randomize the physiotherapeutic intervention.